Customized multiplexing SNP panel for Korean-specific DNA phenotyping in forensic applications - Lim, Seri; Youn, Jong Pil; Hong, Seungbeom; Choi, Dongho; Moon, Seohyun; Kim, Wook; Han, Myunsoo; Hwang, Seung Yong (Genes & genomics, 2017)
Due to the recent growth of the alien population in Korea, tracking the ethnic origin of human specimens has gained importance in genetic forensics. To address this issue, we developed a method to analyze single nucleotide polymorphisms (SNPs) based on next-generation sequencing (NGS) technology, which is now being used for personal identification in forensics. We designed a panel of 153 Korean-specific high-performance multiplexed SNPs and performed NGS using 233 DNA samples collected from eight different ethnic groups around the world. Eight Korean-specific genetic markers (rs28777, rs1010872, rs6043841, rs6034433, rs885479, rs2503107, rs4530059, and rs214955) that were screened showed significant variability among the ethnic groups. Three markers were novel SNPs that were absent from our multiplexed SNP panel, and two markers were associated with specific phenotypes. Our high-performance multiplexed SNP panel allows efficient screening of Korean-specific SNP alleles in populations that are genetically similar to the Korean population (e.g., Japanese and northeast Asians including Chinese and Eurasians), which will be useful for personal identification, paternity testing, and forensic investigations.